Third year La Salle University nursing students' perceptions on psychiatric duty - Fernandez, Gretchen R. (2009)
Psychiatric nursing is a specialty of nursing profession in which the focus of the nurse is directed toward the promotion of mental health... minimization of effects of mental disorders (Worret et al, 2007). Sixty Nursing students who have had psychiatric duty participated in this study. A researcher-made questionnaire was used in gathering pertinent date for the study. It was made up of statements pertaining to their perceptions about their psychiatric ward duty.
Keywords: Nursing; Nursing students